The effect of Zn content on the age-hardening response and precipitation behavior for Al–8Si-0.6Mg-0.1Cu alloys - Lili Hu; Chenggang Wang; Feng Li; Jingqi Zhang; Maohui An; Jinguo Wang; Ruifang Yan (Journal of Materials Research and Technology)
In present study, the effect of Zn addition on the age-hardening response and precipitation behaviour for Al–8Si-0.6Mg-0.1Cu alloys is investigated. The results indicate that the incorporation of Zn accelerates the age-hardening of the Al–8Si-0.6Mg-0.1Cu alloys. With growing Zn content, the number density of β'' phase tends to enlarge, and the average length and average diameter keep decreasing, which lead to a prominent improvement in strength of the alloys. The addition of Zn not only refines the α-Al grains and the GBPs, but increases the inter-particle spacing of the GBPs, which has a beneficial effect on the elongation of the alloy. Compared to the 0Zn alloy, the elongation of the 0.9Zn alloy and the 3.6Zn alloy is increased by 57% and 31%, respectively. For the sample of 3.6Zn under the peak aging state at 180 °C, the precipitation behaviour is changed, which appear the Mg–Zn precipitates. However, for the sample of 0Zn and 0.9Zn, the precipitates consist of β'' phase and trace Q′ phase, the Mg–Zn precipitation phase is not found in the microstructure. Finally, a precipitation schematic is proposed based on the precipitation behaviour of the three alloys, which reveal the evolution of the microstructure of the Al–8Si-0.6Mg-0.1Cu-XZn (X=0, 0.9, 3.6) alloy.